Dampak Pelatihan Konstruksi Bangunan Tahan Gempa Terhadap Perbaikan Kinerja Buruh Bangunan - Herman, Nanang Dalil; Yustiarini, Dewi; Maknun, Johar; Busono, Tjahyani (INVOTEC, 2010)
This research aim to re-build labours capacity on concept and knowledge about housing throughconstruction workshop in endure building from earthquake. The result from this research found thatknowledge of participant had been increase to 41% (fourty one percents) through the workshop.